Analisis Penanganan Kargo Pt. Angkasa Pura Logistik Bandar Udara Internasional Juanda Surabaya Jawa Timur - Sheila Monica Anggraeni; Desiana Rachmawati (CV. Multi Kreasi Media, 2022)
The need for transportation of goods has become a major need, every individual needs a fast and safe transportation of goods to ensure that the goods sent arrive at the right time and place. Cargo handling activities that occur in the warehouse have procedures that must be implemented by both cargo officers and cargo shippers. With the need for sending and receiving goods, cargo handling parties meet the needs of company customers who handle passengers, baggage, cargo, and post during pre-flight and post-flight. This study aims to: 1). Knowing the suitability of cargo handling PT Angkasa Pura Logistik Juanda International Airport Surabaya, East Java. 2). Knowing what are the obstacles in handling cargo at PT Angkasa Pura Logistik Juanda International Airport, Surabaya, East Java. 3). Knowing the attitude of officers in dealing with obstacles to the cargo handling process of PT Angkasa Pura Logistik Juanda International Airport, Surabaya, East Java. This research uses qualitative research with descriptive method . where the technique used in the form of data collection is done by conducting interviews with sources, observation and documentation. With the process of data reduction analysis obtained from the field in the form of a summary, selecting the main things and focusing on the important things. The results showed that: 1). Cargo handling in accordance with the SOP set by PT Angkasa Pura Logistik. 2). The obstacles in the cargo handling process can be overcome by the officers. 3). The attitude of the officers in dealing with cargo handling problems is very professional.